Current trends in the management of thyroid eye disease. Issue 6 (November 2015) - Rao, Rohini; MacIntosh, Peter W.; Yoon, Michael K.; Lefebvre, Daniel R.
Abstract : Purpose of review: The present review summarizes the body of literature concerning the medical and surgical treatment of thyroid eye disease (TED) from 1 January 2014 through 30 March 2015. Recent findings: Corticosteroids continue to be the primary medical therapy for TED. Recent research has offered insight into potential differences between oral corticosteroid and intravenous corticosteroid treatment regimens in terms of efficacy and side-effect profiles. Steroid-sparing medications, for example, rituximab and others, are an area of active study. There has been renewed interest in the role of radiation therapy as a nonmedical treatment for TED with some promising data. The use of balanced orbital decompression techniques have become popular, although the data regarding postoperative diplopia are mixed, and 'fat decompression' offers an alternative or an augmentation to bony decompression. Stereotactic image guidance is a useful adjunct to orbital decompression surgery. Summary: TED continues to be a difficult condition for the patient to cope with and for the clinician to treat, and recent research builds on the present foundation of knowledge and treatments, but unfortunately does not offer paradigm-shifting information at the present time.